Content of protein oxidative modification products and nitrogen monoxide metabolites in the kidneys and myocardium of rats with streptozotocin-induced diabetes in dynamics of cerebral ischemia-reperfusion - O. V. Tkachuk; S. S. Tkachuk; V. F. Myslytskyi; V. P. Gavaleshko; O. V. Yasinska; M. A. Povar; S. V. Boshtan; T. P. Savchuk (Kazimierz Wielki University, 2018)
Introduction. Acute disorders of cerebral circulation similar to diabetes mellitus (DM) cause long-term multiple organ effects, although pathogenesis of internal organs injury in association with DM and cerebral ischemia-reperfusion has not been investigated completely. The aim of the study. To study the dynamics of the content of protein oxidative modification and metabolites in the myocardium and kidneys of rats with DM complicated by cerebral ischemia-reperfusion. Results. The content of protein oxidative modification products in the tissues of the kidneys and myocardium and the content of nitrogen monoxide metabolites in the cortical and medullary substance of the kidneys were found to decrease in the early ischemic-reperfusion period in rats without DM. In rats with DM early post-ischemic changes are restricted by the increase of nitrogen oxide metabolites content in the renal medullary substance. Total remote changes of the examined parameters are found in the myocardium of rats without DM and the medullary substance of the kidneys in rats with DM. Conclusions. Diabetes mellitus eliminates or restricts the reaction of the examined indices peculiar for control animals in both periods of observation in all the examined tissues except the medullary substance of the kidneys on the 12th day of the post-ischemic period.